OUTCOME OF STAGE T1 RENAL CELL CARCINOMA TREATED WITH PARTIAL NEPHRECTOMY: INITIAL EXPERIENCES FROM A TEACHING HOSPITAL IN BANGLADESH - Morshed, Md. Selim; Al-Asad, Hafiz; Alam, Mohammad Saruar; Lutful Hasan, Abu Naser Md.; Belal, Md. Towhid; Hossain, AKM Shahadat; Zaman, Sojib Bin (Public Health of Indonesia, 2018)
Background: Renal cell carcinoma accounts for 85% of all solid tumors of the kidney. For many years, radical nephrectomy was the standard treatment for RCC. Partial nephrectomy has gradually replaced radical nephrectomy over the past decade, especially for T1 stage renal cell carcinoma. However, the benefit of partial nephrectomy on oncologic outcomes is not well known.Objective: to investigate the clinical outcome of partial nephrectomy on T1 renal cell carcinoma. Methods: This prospective observational study was conducted in a single unit of urology department of Dhaka Medical College Hospital, Bangladesh from the period September 2014 to September 2017. Fourteen patients underwent partial nephrectomy during this period with renal mass based on eligibility criteria. Two follow up was done at three months and six months. Result: Mean age of the patients undergoing surgery was 52.0± 3.8 (46.0 to 57.0 years) years. For the majority of the patients, tumour size was in a range of 3-7 cm. Average operative time was 90 minutes and mean ischaemic time was 16.5 ± 4.6 minutes (14.5 to 21.0 minutes). Histopathological reports correlated with clinical diagnosis and showed adequate surgical clear margin in every case.  There was no recurrence of tumour noticed during the two follow up periods. The different investigation did not reveal the impaired renal functional test during the follow-up period. Conclusion: The clinical outcome of partial nephrectomy was found better in this study. Partial nephrectomy has the potential to replace radical nephrectomy for managing T1 tumours. However, there are some controversies regarding the post-operative oncological outcome. More studies are recommended to investigate the effect of partial nephrectomy for T1 tumours.